3(2x+3)+6=5(2x+3)
6x+9+6=10x+15
6x+15=10x+15
15=4x+15
30=4x
30/4=x
15/2=x or x=15/2
2006-11-09 13:28:48
·
answer #1
·
answered by kool5aban 2
·
0⤊
0⤋
The procedures above are all correct. However, just in case you didn't understand where 6x +9 +6 = 10x +15 came from...You have to distribute the 3 through the parentheses by multiplication.
3 times 2x + 3 times 3. This gets rid of the parentheses. Do the same for the other side of the equation.
2006-11-09 22:23:15
·
answer #2
·
answered by schlance2003 2
·
0⤊
0⤋
3(2x+3)+6=5(2x+3)
6x+9+6=10x+15
6x+15=10x+15
4x=0
x=0
so The answer is x=0 .
You can get it . I wish this could help you to find out the answer .
2006-11-10 01:50:34
·
answer #3
·
answered by Chong Sian C 3
·
0⤊
0⤋
3(2x +3) + 6 = 5 (2x + 3)
6 = 5 (2x +3) - 3 (2x+3) = (5-3)(2x+3) = 2 (2x +3)
6= 2 (2x+3) = 4x + 6
0=4x
x=0
15=15 CHECK
2006-11-09 21:30:09
·
answer #4
·
answered by Kyler 1
·
0⤊
0⤋
6x + 9 + 6 = 10x + 15
Subtract 6x from both sides (so the only x term is on the right) and subtract 15 from both sides (only constants on the left), then solve for x. You should get x = 0 as the solution.
2006-11-09 21:27:46
·
answer #5
·
answered by Hy 7
·
0⤊
0⤋
6x+9+6=10x+15
6x+15=10x+15
0=4x
x=0
2006-11-09 21:39:49
·
answer #6
·
answered by OK123 5
·
0⤊
0⤋
6x + 9 + 6 = 10x + 15
10x - 6x + 15 - 15 = 0
4x = 0
so x=0
helped?
2006-11-09 21:28:07
·
answer #7
·
answered by Migrant 2
·
0⤊
0⤋
do the same kind of thing that i gave you the other answer for.... same method, just different numbers....
2006-11-09 21:30:51
·
answer #8
·
answered by camm300 4
·
0⤊
0⤋